An Affordable Internet of Things Solution for Health Monitoring Utilizing ESP32 Technology - Ahmed Salem Daw Alarga; Elhadi Elfitory Algarai; Nuria Mohamed Haider; Abdussalam Ali Ahmed (African Journal of Advanced Pure and Applied Sciences, 2024)
The Internet of Things (IoT) technology has become inevitable in various fields due to its prominent role in achieving speed and accuracy in business performance. One of the most important fields in which IoT technology has contributed to its development and brought about a technological revolution is the field of healthcare. IoT technology has contributed to transferring patient data and displaying it to doctors remotely without the need for the doctor to be present next to the patient. In this paper, a healthcare system based on IoT technology was designed using an ESP32 board, an LM35 sensor, and a MAX30102 sensor, which is characterized by being inexpensive and easy to use. This system transfers a set of parameters specific to the patient’s condition to a graphical user interface (GUI) designed on the Blynk platform, so that this interface allows the doctor following up on the patient’s condition to review these parameters and then diagnose the patient’s condition without the need to be with him. The system was tested and good results were obtained, as the parameters specific to the patient’s condition were displayed on the GUI in real time.